Indirect density tests for thin asphalt overlay – part 1: review. Issue 5 (18th October 2021) - Xu, Yi; Nicklin, Samuel; Bull, Jack; Widyatmoko, Iswandaru
Abstract : Quality in construction of asphalt pavements plays a significant role in long-term durability. In situ density is a key parameter in construction quality and there are several available test methods. However, there are questions as to whether a particular test provides density values (referred to as 'quality assurance') or density changes (referred to as 'quality control'). This paper presents findings from a literature review of indirect density testing on asphalt pavements. A specific interest is on thin overlays in the 30–50 mm thickness range typically used in the UK. Indirect test methods include nuclear density gauge, electromagnetic instruments, ground-penetrating radar and step frequency radar. The advantages and limitations of these methods for thin asphalt in situ density measurement are discussed in this paper.